A Preventive Role of Exercise Across the Coronavirus 2 (SARS-CoV-2) Pandemic - Wang, Meizi; Baker, Julien S.; Quan, Wenjing; Shen, Siqin; Fekete, Gusztáv; Gu, Yaodong (Frontiers in Physiology, 2020)
The coronavirus 2019 (COVID-19) pandemic has posed a significant threat to human health around the world. A severe risk of infection has been observed in elderly populations. In addition, individuals with obesity and obesity-related comorbidities have also been identified to be at a higher risk of infection for COVID-19. We have attempted here to provide evidence in support of exercise management as a prevention strategy for improving health and minimizing the effects of COVID 19. Therefore, exercise type, benefits and volume are summarized in an attempt to provide guidelines for the general population. In terms of exercise effects, there are multiple benefits of exercise related to human health. These include, decreases in adipose tissue, improvements in cardiorespiratory fitness and enhanced metabolic homeostasis. With respect to the amount of exercise performed individuals should exercise at a moderate intensity for at least 150 min/wk as an initial target. Increases in intensity and duration of exercise training is necessary for significant fitness benefits, weight loss and prevention of weight regain. In relation to walking, 10,000 steps/day at a rate of 64-170 steps/minute for at least 10 minutes duration is reasonable for healthy adults. For exercise type, a combination of resistance training (RT), aerobic training (AT) as well as vigorous intensity training (VIT) incorporated with moderate intensity training (MIT) can be recognized as an optimal exercise mode for health benefits. Aerobic training and MIT should be viewed as a basis for exercise in combination with appropriate volumes and types of RT and VIT. Activities should be performed according to professional guidelines and advice. These measures if implemented may have reduced infection rates, underlying pathologies and contributed to increased mortality in association with the COVID 19 pandemic.